ANALYSIS OF EDUCATION POLICY IN REDUCE THE PHENOMENON OF STUDENTS DROPOUTS IN VARIOUS REGIONS IN INDONESIA - Winarti; Eddy Haryanto; Masbirorotni (RADJA PUBLIKA, 2026)
The phenomenon of school dropouts in Indonesia is a complex issue influenced by various multidimensional factors. This study aims to identify the factors causing school dropouts and analyze government policies to reduce the dropout rate. The method used is Systematic Literature Review(SLR). The analysis results show that economic factors are the most dominant cause, mainly due to limited family income, high education costs, and the demand for children to contribute to the family economy. In addition, social and cultural environmental factors, such as low public awareness of the importance of education, certain cultural values, and the influence of the surrounding environment, also contribute to increasing the dropout rate. Individual factors, such as low motivation to learn, interest, and academic ability of students, are also factors in dropping out of school. On the other hand, the government has implemented various policies to reduce the dropout rate, including the School Operational Assistance (BOS/BOSP), the Smart Indonesia Program (PIP), the free education and 12-year compulsory education policies, and regional-based programs supported by the commitment of local governments. Furthermore, strengthening data collection systems, social interventions, and cross-sector collaboration are also important strategies in addressing this issue. Although these policies have had a positive impact, their implementation still faces various obstacles, such as inaccurate targeting, uneven distribution of aid, and suboptimal coordination between institutions. Therefore, strengthening policy implementation, increasing public awareness, and a more comprehensive and sustainable approach are needed to reduce the dropout rate in Indonesia.